Exploring genetic diversity and selection signatures in indigenous African cattle breeds - Friedrich, J.; Bailey, R.; Talenti, A.; Marshall, Karen; Prendergast, J.; Wiener, P. (Wageningen University & Research, 2022)
African cattle are a fascinating resource for exploration of genetic diversity due to their complex history and their adaptation to diverse environments. As a consequence of taurine and indicine ancestries and selection pressure from various environments as well as from humans, over 150 African cattle breeds exist today with remarkable genotypic and phenotypic diversity. We analysed whole-genome sequence data of over 100 African cattle comprising 9 breeds and calculated within- and between-breed population statistics to characterise genetic diversity and identify selection signatures. We found overlapping selection signatures between indigenous African breeds, with the longest selection signature on BTA10. The greatest genetic differentiation from other breeds was observed for the N?Dama and Boran breeds, potentially mirroring their high proportion of taurine and indicine ancestry, respectively. Genomic regions that are highly differentiated between breeds suggest candidate regions for associations with important adaptation and production traits.